Reação em cadeia da polimerase (PCR) e hemocultura em cães com suspeita de sepse - Silveira, Marcelo Marques da (2018)
Sepsis is characterized by the presence of organic dysfunction secondary to the dysregulated systemic inflammatory response, associated with an infection with high mortality rates. Blood cultures based on microbiological isolation are highly specific indicators for diagnosis of bloodstream infection, but within their limitations are the time to close the diagnosis and the low sensitivity that may delay treatment. The objective of this study was to compare the Polymerase Chain Reaction (PCR) and blood culture for the diagnosis of bacterial and fungal bloodstream infections in dogs with suspected sepsis. We analyzed 88 blood samples from dogs with suspicion of sepsis through blood culture, PCR and antibiogram tests. Twenty (22.7%) samples of bacterial isolates were found in blood cultures and no samples were positive for fungi. Most bacterial isolates were sensitive to ceftriaxone (78.2%) and resistant to clindamycin (78.2%). Through PCR analysis, bacterial DNA was detected in 46 animals (52.3%), while fungal DNA was present in a sample (1.1%). PCR may be an auxiliary tool in the rapid diagnosis of bloodstream infections, but blood culture as the gold standard, it is important to isolate the infectious agent to detect bacteremias, and perform antibiograms to establish adequate therapy, since administration antibiotic can cause selection of resistant strains.